Peran Orang Tua dalam membentuk Religiusitas Anak pada Jemaat Gereja GKI Waliyauw Komba Kampung Yobeh - Walilo, Thimeus; Lefaan, Avelinus (JURNAL EKOLOGI BIROKRASI, 2024)
The role of parents in the development of children's personality is very important, especially in the formation of religious personality. Parents are the first means through which a child undergoes socialization and the formation of the child's personality. Because parents are a reflection of the child, it is expected that religious education in children will succeed in shaping the child's personality. The purpose of this study is to find out what are the roles of parents in fostering children's religiosity, what values children get from the religiosity, and how children are influenced in the practice of religiosity in the community. The location of this research is Yobeh village in Senthani district of Jayapura Regency. This research is a descriptive qualitative research. The data collection techniques used are in-depth interview, observation, and documentation. Data analysis includes the stages of data exploration, data classification, data validation, and conclusion drawing. The result of this study is that the role of parents is still not fully implemented. This is because there are still many parents who delegate their parenting role to other institutions. There are several reasons why this happens, because many parents do not have time to provide full care, because they are busy earning a living. But there are also parents who want to directly shape the religious role of their children, so there are also parents who teach their own religious education to their children. Evidently, parents directly or indirectly have a very large role in shaping the character and personality values of their children.